Integrating Sustainable Concepts into Blended Learning and Interactive Game System Design - Peng-Wei Hsiao; Zheng-Qing Wang (Engineering Proceedings, 2025)
Food is essential for sustaining human life. While people love delicious food, they often neglect the care for it. One of the most commonly wasted foods is bread. There has not been much research on bread waste. Carbon emissions from bread are not less than those from meat products. Therefore, it is necessary to integrate sustainable concepts with mixed learning approaches into a mixed reality (MR) interactive system, focusing on bakeries. We conducted field research and observations of leftover bread from eight local bakeries, categorizing and photographing them. We combined knowledge and teaching about carbon emissions with interactive games to help users understand the relationship between bread and carbon emissions. Users can learn about relevant knowledge and content by playing the MR game. The interactive game provides a reference for sustainability research in the future.